Metrics of application performance. Mean, standard deviation, and range of recall, precision, and calculated F1-score of all four tested clinicopathologic findings across all testers of the application for extraction of necropsy data from the Wildbase Pathology Register, DEE. - Stefan Saverimuttu (20882325) (2025)
Metrics of application performance. Mean, standard deviation, and range of recall, precision, and calculated F1-score of all four tested clinicopathologic findings across all testers of the application for extraction of necropsy data from the Wildbase Pathology Register, DEE.